Implications of Human Trafficking on the Romanian Society - Camelia Elena Nichita; Miruna Mutu; Gabriela Bologa (Agora International Journal of Economical Sciences (AIJES), 2019)
In order to raise awareness of the phenomenon of trafficking in human beings among different institutions (law enforcement, child protection, NGOs) and to improve the measures they can take, the article aims to identify how severe is the phenomenon of human trafficking in Romania. We also want to identify the repercussions of this phenomenon as well as to identify the solutions at political and legislative level in order to reduce or even combat this phenomenon.
Keywords: 330